Contemporary nuclear physics - National Seminar on'Contemporary Nuclear Physics' (2003? : Institute of Physics, Bhubaneswar); Praharaj, C. R.; Institute of Physics (Bhubaneswar, India) (New Delhi : Narosa Pub. House, 2003)
Contributed papers presented at the National Seminar on'Contemporary Nuclear Physics', held at the Institute of Physics, Bhubaneswar
Includes bibliographical references
Keywords: Nuclear physics -- Congresses